Interprofessional Education: Learning Method and Core Competencies in Medical Students in Asia - Rachmawati, Alfira; Makkiyah, Feda Anisah; Bustamam, Nurfitri; Muktamiroh, Hikmah (Universitas Gadjah Mada, 2024)
Background: Interprofessional collaboration is a partnership among health professionals that supports more comprehensive, confident, and safe healthcare. Collaboration competence in Indonesian health worker still needs to be improved. Interprofessional education is an effort to realize interprofessional collaboration. Aims: This study aims to describe the implementation of interprofessional education learning for preclinical medical students in Asia by identifying learning methods, learning outcomes and challenges.Methods: Scoping reviews were conducted in this study. Articles were sourced from Proquest, PubMed, and Taylor & FrancisOnline using Population, Intervention, Comparison and Outcomes (PICO Framework). In the identification process, 737 articles were found and screened according to inclusion criteria. Nine articles were assessed for eligibility using the Joanna Briggs Institute Critical Appraisal Tools Checklist for Quasi-Experimental Studies and seven articles were obtained.Results: Learning methods such as simulation-based learning, problem-based learning, didactic learning, community-based learning, team-based learning, and shadowing were found. Learning outcomes vary in each article because objectives, measuring instruments, and selection of activities are also varied.Conclusion: Interprofessional education improves students' ability to collaborate. Learning methods and outcomes varied according to the objectives and design of the program in each institution. The challenges encountered were logistical, student diversity, facilitator skills, and cultural barriers.